The speckled monster a historical tale of battling smallpox - Carrell, Jennifer Lee (Plume Book, 2003)
The Speckled Monster tells the dramatic story of two parents who dared to fight back against smallpox. After barely surviving the agony of smallpox themselves, they flouted eighteenth-century medicine by borrowing folk knowledge from African slaves and Eastern women in frantic bids to protect their children. From their heroic struggles stems the modern science of immunology as well as the vaccinations that remain our only hope should the disease ever be unleashed again. Jennifer Lee Carrell transports readers back to the early eighteenth century to tell the tales of Lady Mary Wortley Montagu and Dr. Zabdiel Boylston, two iconoclastic figures who helped save London and Boston from the deadliest disease mankind has known.